Features of DC magnetron sputtering of mosaic copper-graphite targets - Mitin, Valery; Mankelevich, Yury; Pal, Alexander; Rakhimova, Tatyana; Ryabinkin, Alexey; Serov, Alexander; Mitin, Alexey; Krasnobaev, Nikolay (International Conference on Plasma Surface Engineering, 2013)
Not available